Implementasi Media Talaqqi Qiraah Al-Quran Di Masjid Al-Jihad Mabar, Medan Deli - Mavianti Mavianti; Muhammad Jaka Samudra; Rizky Awwalul Ramadhan; Saipul Azhari Pane (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
As Muslims, it is obligatory for us people to learn how to read the Quran. The talaqqi method is proven to be the most complete in teaching the correct reading of the Qur'an and most easily accepted by all. In modern times, especially during the covid-19 pandemic, which is still endemic in Indonesia, we too can learn qiraat Al-Quran by indirectly meeting the teacher in a dzhohir, plus this epidemic that has not gone away (covid-19) makes us vulnerable to face to face with someone, even advised to self-isolate in their respective homes. This study aims to find out how to implement, develop and how much influence the Media Talaqqi Qira'ah Al-qur'an has in the Al-jihad Mosque in Medan Deli during the Covid-19 pandemic. This study uses a qualitative research approach where qualitative research is the scientific method. With the appropriate learning media to apply the Talaqqi method, we can meet the teacher through audio/video/or audio-visual. Al- Jihad Mosque children so that their tongues get used to saying the correct lafadz, we suggest saying it often in daily activities. Using media in Talaqqi qiraat Al- Quran can be used especially during this covid-19 pandemic, children at Masjid Al-Jihad Kel. Mabar, District. Medan Deli is very much familiar with using technology such as cell phones, who can directly communicate either by voice or video with the teacher to check the reading.